ECIR 2018: Text2Story Workshop-Narrative Extraction from Texts - Jorge, Alípio Mário Guedes (2020)
The 1st International Workshop on Narrative Extraction from Texts (Text2Story 2018) was held in conjunction with the 40th European Conference on Information Retrieval, ECIR 2018, Grenoble on the 26th March 2018. The workshop aimed to help foster the collaboration of researchers on a wide range of multidisciplinary issues related to the text-to-narrative- structure. The program consisted of two keynote talks, six research presentations, a poster session and a slot for demo presentations. This report briefly summarizes the workshop.